Design And Development Of Gas Argon Purging System - Ooi, Seng Yeong (Universiti Sains Malaysia, 2006)
Using a single pneumatic control valve with PI feedback controllers test, a method is proposed to design and develop to the current gas argon purging system while to identify that the present 6 different kinds of digital control valve may not give the actual flow rate to the liquid steel purging system. In the present work, a method is proposed, by incorporating the ABB PLC (Programmable Logic Controller) to explain how well the purging control system is being controlled. A method is proposed to estimate the accuracy of the system by implementing PI algorithm. Two MatLab simulation results are given on stable first second order and third order plus unity feedback transfer function models. The estimated PI models are compared with the real time implementation of PI controller in gas argon purging system. PI controllers are designed for the identified model and for the actual system. The proposed method gives performance close to that of the actual system. Using an appropriate pneumatic control valve is much concerned in this test by calculating out its coefficient of valve (Cv) by mean to identify higher flow rate may require higher value in Cv while lower flow rate requests for lower Cv. By the way, a test shows that by using wrongly control valve, the PI controller would produce intangible result. Using AMPL (ABB Master Program Language) with ABB PLC controller is much different from Siemens or Mitsubishi PLC programming which they intended to use ladder diagram as function for the control system. AMPL is used in two ways of connection of its programming, first is Data Base, and second is PC element. Data Base is held on intermediate between PC element and hardware’s(input card and output card of PLC) connection. Mircosoft Workgroup 3.11 operating system is used to transfer the AMPL programming to the PLC. 2 analogue signals and 4 digital signals are used in the program to manipulate the control system. The analogue signals will be connected to analogue input card and output card while digital signal will be placed at only digital input card, because there are 4 digital input signals can be used to generate 16 steps setting for the gas purging system. The PI controller designed on the system identified by the proposed method gives a performance better than the present working system.